Needs Analysis for Implementing Distance Education and Digital Transformation in Islamic Boarding School Learning in Garut Regency - Dadang Abdul Hamid Hakim; Iman Nasrullah; Dian Rahadian (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to analyze the need for implementing distance education and digital transformation in Islamic boarding school learning in Garut Regency. The background of this study is based on the demands of information technology developments that encourage educational institutions, including Islamic boarding schools, to adapt to digital-based learning systems. This research method uses a qualitative approach with a descriptive-analytical method, which aims to understand in depth the phenomenon of the need for implementing distance education and digital transformation in Islamic boarding school learning. Data collection techniques through interviews, observations, and documentation in several Islamic boarding schools in Garut Regency. The results show that distance learning in Islamic boarding schools in Garut Regency has been implemented through the use of digital technology with a blended learning pattern, but is still adaptive and has not been systematically integrated in the curriculum, methods, and evaluation aspects. Supporting factors include the availability of technology, internet access, and digital literacy of educators, while inhibiting factors include limited infrastructure, gaps in teachers' digital competencies, student readiness, and the absence of comprehensive institutional policies. This study produces a digital transformation-based distance education implementation model that includes dimensions of policy, infrastructure, human resource competencies, learning processes, and evaluation and monitoring, as a basis for developing more effective, adaptive, and sustainable learning.